The Integration of the LPSK into the Criminal Justice System: The Urgency of Witness and Victim Protection Amidst an Illusion of Criminal Procedure Law Reform - Fathan, Robbi; Rivanie, Syarif Saddam; Karim, Muhammad Said; Iskandar, Ismail; Sriyana, Sriyana; Halim, Hamzah (SIGn Journal of Social Science, 2025)
Indonesia’s criminal justice system confronts a fundamental paradox. Constitutional guarantees of citizen protection clash with the architecture of Law Number 8 of 1981, which is inherently offender-oriented and retributive in its paradigm. Ironically, the reform effort through the Criminal Procedure Code Bill, projected as a solution, risks creating a new “illusion of protection.” The draft Bill presents a seemingly progressive showcase of witness and victim rights. However, it simultaneously fails to provide an integrated enforcement mechanism and even introduces norms that could create systemic disharmony. This research aims to analyze the urgency of the problem and to formulate a holistic integration model for LPSK as a response to this systemic malady. Employing a hybrid legal research method that combines a juridical-normative analysis of the regulatory framework with a qualitative approach through an in-depth interview with an LPSK senior expert, this study finds that the LPSK’s structurally isolated position has led to serious institutional friction and ambiguous authority, despite its proven crucial role in strategic cases. Therefore, it is concluded that the required solution is a structural transformation. This study recommends a systemic integration model via two pathways: an imperative revision of the Criminal Procedure Code Bill, or the strengthening of the LPSK through an amendment to Law Number 13 of 2006 as a synchronized lex specialis, to ensure the realization of a criminal justice system that is substantively centered on witnesses and victims.